Validação de ensaio multiplex por reação em cadeia da polimerase (PCR) seguida de hibridização reversa (dot blot) em espécimes do trato respiratório inferior - Igor César de Oliveira Sousa (2022)
Pneumonia is an acute inflammatory disease of the lungs, caused by an infectious/inflammatory disorder of the lung parenchyma, which affects, especially the pulmonary alveoli. Clinical parameters and laboratory values ​​are sensitive for diagnosing pneumonia but these parameters are nonspecific for bacterial infections. Microbiological examination of samples obtained from the lower respiratory tract is well established as a reliable method. However, cultures generally take 2 to 5 days to provide definitive results. This study was designed to optimize a protocol for the diagnosis of etiological and resistance genes for future implementation in routine laboratory diagnosis of pneumonia, through standardization and methodological validation of a molecular panel of bacterial genes using respiratory samples.The study was carried out with 53 respiratory samples and the molecular results were compared with the conventional microbiological culture, following the recommendations of regulatory agencies for the validation of analytical methods. The results of the technical analysis achieved 100% reproducibility and repeatability of the method. Clinical results showed the prevalence of Streptococcus spp (17.39%), Pseudomonas aeruginosa (15.65%) and Klebsiella pneumoniae (14.78%) with 60.86% of polymicrobial infections. The main resistance markers identified were the KPC (25.35%) and MecA (16.90%) genes. The overall clinical sensitivity was 100%, with a specificity of 99.84%. Time for diagnosis for microbiological cultures took an average of 92.3 hours versus an average of 7.1 hours for genotypic identification. The results showed good agreement with conventional culture, excellent repeatability, reproducibility and high analytical and clinical precision in detecting microorganisms and resistance markers in pneumonia-related lower airway samples. These results reinforce the idea that, in the future, the gold standard for the diagnosis of pneumonia may be the combination of clinical judgment, laboratory values and the results of molecular panels